(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2019)
People with disabilities are in most cases treated as subject of donations and social welfare. In Bangladesh, though approximately 15 million people suffer from various disabilities and a large portion of population of Bangladesh comprises of women with disabilities (WWD) living in an environment and society dominated by male. They are been discriminated against, socially marginalized and do not have access to basic social services. Moreover they are been victims of different crimes including domestic violence, rape or dowry which inflicts them severe loss and sufferings. Considering this situation, this article firstly aims to find out the status of WWD under human rights perspective considering major national and international instruments. Then it tries to review the ambit of legal protection of the women disabled persons in Bangladesh along with its major defaults. Lastly it recommends how the rights of WWD can fully be warranted in reference to best practices followed by other progressive states.